Bjerke_et_al_Nord_J_Bot_2018_Fig_3_ new_leaves - Bjerke, Jarle; Wierzbinski, Grzegorz; Tømmervik, Hans; Phoenix, Gareth; Bokhorst, Stef (Dryad Digital Repository, 2018)
Temporal changes in contents of chlorophyll concentration (Chl), nitrogen (NBI) and flavonoids (Flav) in new leaves of Vaccinium myrtillus from May 2016 to early autumn in late August 2016.